An 18 Multi‐InDels panel for analysis of highly degraded forensic biological samples. Issue 9 (12th January 2021) - Li, Jienan; Lin, Lin; Jiang, Bowei; Wang, Chudong; Zeye, Moutanou Modeste Judes; Wen, Dan; He, Wei; Qu, Weifeng; Liu, Ying; Zha, Lagabaiyila
Abstract: DNA genotyping from trace and highly degraded biological samples is one of the most significant challenges of forensic DNA identification. There is a lack of simple and effective methods for genotyping highly degraded samples. In this study, a multiple loci insertion/deletion polymorphisms (Multi‐InDels) panel was designed for detecting 18 autosomal Multi‐InDels through capillary electrophoresis (CE) with amplicon sizes no longer than 125 bp. Studies of sensitivity, degradation, and species specificity were performed and a population study was carried out using 192 samples from Han populations in Hunan province in the south of China. The combined random match probability (CMP) of these 18 Multi‐InDels was 3.23 × 10 –12 and the cumulative probability of exclusion (CPE) was 0.9989, suggesting this panel could be used independently for human identification and could provide efficient supporting information for parentage testing. Complete profiles were obtained from as low as 62.5 pg of total input DNA after increasing the number of PCR cycles. Moreover, all alleles were detected from artificially highly degraded DNA after 80 min of boiling water bath treatment. This 18 Multi‐InDels panel is simple, fast, and effective for the forensic analysis of highly degraded DNA.